Hardness and tribological properties of electrodeposited Ni–P multilayer coatings fabricated through a stirring time-controlled technique - Nujira Kothanam; Komsak Harachai; Jiaqian Qin; Yuttanant Boonyongmaneerat; Napat Triroj; Papot Jaroenapibal (Journal of Materials Research and Technology, 2022)
Ni–P multilayer coatings were deposited on the surfaces of low-carbon steel by direct current electrodeposition through a stirring-time controlled technique (STT). The microstructure, hardness, friction coefficient and wear properties of the deposits were investigated. Scanning electron microscopy (SEM) in back-scattered electron mode revealed multilayer structures of Ni–P coatings fabricated by repeatedly turning the magnetic stirrer in the bath on and off. Energy dispersive X-ray spectroscopy (EDS) was employed to quantitatively compare the P content in the alternating layers. The hardness of the Ni–P multilayer coatings was found to be significantly greater than that of monolithic Ni–P coatings. A maximum hardness value of 580 ± 8.7 HV0.1 was found in the sample prepared using the on- and off-stirring periods of 8 and 15 min, respectively. This showed an increased hardness of 20.1% from that of sample prepared with the stirrer turned off. The Ni–P multilayer coatings prepared by STT also had superior wear resistance to that of monolithic Ni–P coatings.